Speechcraft : - Hahn, Laura D. (University of Michigan Press, 1999)
Speechcraft is a multi-book project that includes one core text that can be accompanied by several different workbooks, depending on the needs of the learner. The first workbook to accompany the core text was written with international teaching assistants (ITAs) in mind, and it expands on and contextualizes the content of the core text for ITAs. The second workbook was written for anyone who needs to com-municate effectively in academic settings. All Speechcraft books have been designed for advanced non-native speakers who expect to interact with native speakers in academic and professional settings. These materials provide rules, learning strategies, and contextualized practice in the stress, rhythm, and melody of English words and discourse--the features of English pro-nunciation that most affect intelligibility. For example, students will learn patterns for using stress to highlight contrasts, for connecting words smoothly, and for emphasizing the correct syllable in a word. In the workbooks, students will also apply these patterns to teaching and university contexts (e.g., lectures, discussions, labs, office hours) in guided and communicative exercises.